Solution-focused Brief Counseling Guidebook to Reduce Student’s Academic Procrastination - Ayu Putu Dewanti Arsari; Kadek Suranata; I Ketut Gading (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study aims to develop and evaluate solution-focused brief counseling guidebook as an instrument to reduce student’s academic procrastination. This research and development conducted by following 4D model by Thiagarajan that consist four stages of development namely (1) define, (2) design, (3) development, and (4) disseminate. Five experts are involved as judges to evaluate the content validity of counseling guidebook. The piloting study were conducted in one group pretest-posttest design to evaluate the effectivity of counseling guidebook to reduce student’s academic procrastination. Result of expert judgments were analyzed using formula Lawshe and show that the counseling guidebook has “very special” content validity index ( CVI = 1). Based on the results of piloting study, it was reported that counseling guidebook developed in this study effective in decrease student’s academic procrastination levels. The results of this study contribute to the development of guidance and counseling services.